PENERAPAN BUY BACK GUARANTEE DALAM AKTA PERJANJIAN PENGIKATAN JUAL BELI YANG DIBUAT OLEH NOTARIS - Tutuarima, Janesia; Tjempaka, Tjempaka (Universitas Ekasakti, 2023)
The binding sale and purchase agreement made before a notary is one of the authentic proofs in the form of a preliminary agreement on the sale and purchase of land rights which will then be made a sale and purchase deed before the land deed making official. The problem examined in this study is regarding the application of buy back guarantees in the deed of binding sale and purchase agreement made by a notary. The type of research used is legal research. The research method is a statutory approach originating from data collection obtained from secondary data, then analyzed using qualitative analysis methods. The results of this study ultimately provide an answer that the repurchase rights that exist in the PPJB are disputed because they are often considered to be in the form of debt agreements, for that the Notary must really pay attention to the needs/interests of the parties because the legal power of the PPJB as authentic evidence in the transfer of rights is very strong, because the deed is a notarized deed that is an authentic deed. The author's suggestion from this study is that it is better for the right to repurchase in binding sales and purchases to be further regulated in laws and regulations, especially those related to land issues, so that parties who use binding sales and purchases as a preliminary agreement in buying and selling land rights are better protected.